Profiling Senyawa Volatil Daging Sapi dengan Berbagai Pengolahan Menggunakan Metode Headspace-GC/MS: The Profiling of Volatile Compounds in Beef with Various Processing Methods Using the Headspace GC/MS - Lia Amalia; Riyani; Sri Widowati; Aji Jumiono; Mardiah Mardiah (Universitas Djuanda, 2026)
Volatile compound profiling is important for understanding the aroma characteristics of beef and supporting the authentication of meat-based products. This study aimed to examine the volatile profile of beef (Bos taurus) processed by boiling, frying, and roasting using the Headspace Gas Chromatography–Mass Spectrometry (HS-GC/MS) method. Round beef samples from five cattle were subjected to the three heat treatments and analyzed based on retention time and peak area to determine the types and relative abundances of volatile compounds. The results showed that boiled beef produced 91 volatile compounds, while fried and roasted beef generated 58 and 56 compounds, respectively. The identified compounds included aldehydes, ketones, carboxylic acids, alcohols, esters, aromatic hydrocarbons, sulfur compounds, alkanes, terpenoids, amides, and amines. Boiling was mainly characterized by compounds derived from mild lipid oxidation, frying by more intensive Maillard reactions, and roasting by advanced Maillard reactions and Strecker degradation. These findings indicate that processing methods influence the volatile composition and aroma characteristics of beef. The HS-GC/MS approach provides valuable information for food authentication.